Does privatization deliver? : Highlights from a world bank conference - Galal, Ahmed, ed. \ Shirley, Mary, ed (Washington : EDI Development Studies, 1994)
Overview, 3. -- A changing course toward privatization, 11. -- Privatization : Lessons from New Zeland, 19. -- Questions and approaches to answers, 27. -- The United Kingdom, 33. -- Chile, 47. -- México, 59. -- Malaysia, 75. -- Winners and losers in privatization, 91. -- Policy implications, 101. -- The jigsaw puzzle, 107